New Insights Into DNA Repair Revealed by NucS Endonucleases From Hyperthermophilic Archaea - Zhang, Likui; Jiang, Donghao; Wu, Mai; Yang, Zhihui; Oger, Philippe M. (Frontiers in Microbiology, 2020)
Hyperthermophilic Archaea (HA) thrive in high temperature environments and their genomic sta¬bility is facing severe challenge due to increased DNA damage levels caused by high temperature. Surprisingly, HA display similar spontaneous mutation frequencies to mesophilic microorganisms, thereby indicating that the former possesses more efficient DNA repair systems than the latter to counteract potentially enhanced mutations under harsh environments. Although a few repair pro¬teins or enzymes from HA have been biochemically and structurally characterized, molecular mechanisms of DNA repair of HA remain largely unknown. Genomic analysis of HA revealed that they lack MutS/MutL homologues in mismatch repair and recognition proteins in nucleotide exci¬sion repair. Endonucleases play an essential role in DNA repair of organisms, including HA. NucS endonuclease, a novel endonuclease recently identified in some HA and bacteria, can act on branched, mismatched and deaminated DNA, suggesting that this endonuclease is a multifunc-tional enzyme that is involved in NER, MMR, and deaminated base repair in a non-canonical manner. However, catalytic mechanism and psychological function of NucS endonucleases from HA have not been completely clarified. In this review, we focused on recent advances in our un¬derstanding of function of NucS endonucleases from HA in mismatch repair, nucleotide excision repair, and deaminated DNA repair, and also proposed a prospect for future studies of these NucS en¬donucleases.